DEVELOPMENT OF THIN CONSERVATION-GRADE PAPER FROM INDONESIAN PAPER MULBERRY - Suranto, Christopher Alma; Sudiono, Sri; Ekarini, Fransiska Dian (Balai Konservasi Borobudur, 2024)
This research explores the development of conservation-grade paper from Indonesian paper mulberry (Broussonetia papyrifera), commonly known as daluang, as a sustainable material for historical artifact preservation. Given the scarcity of locally produced conservation-grade paper in Indonesia, this study investigates the technical feasibility of utilizing daluang fibers in papermaking. The research details the steps of bark extraction, fiber purification, delignification, bleaching, and sheet formation, following traditional papermaking techniques.. Three alkaline solutions (NaOH, Na₂CO₃, and Ca(OH)₂) were employed for delignification, followed by mechanical and chemical characterizations including tensile testing, colorimetry, pH analysis, SEM, and ATR-FTIR. The results demonstrate that NaOH-delignified fibers produce the thinnest paper with improved fiber dispersion, while Ca(OH)₂-treated samples exhibit higher tensile strength and pH stability. The findings show Indonesian paper mulberry's potential as a resource for conservation-grade paper, though further optimizations are needed to enhance fiber distribution and lignin removal for practical conservation applications.